Flutuação populacional e análise faunística de Carabidae e Staphylinidae (Coleoptera) em Jaboticabal, São Paulo - Cividanes, Francisco Jorge [UNESP]; Cividanes, T.M.S. (My University, 2008)
In this study a population survey of Carabidae and Staphylinidae (Coleoptera) adults was carried out with the aim to analyze their populations through faunistic indexes and to determine the influence of temperature, relative humidity and rainfall. The study was conducted in two areas cultivated with soybean/corn under no-tillage and conventional tillage systems and adjacent to a forest fragment and a Pinus stand, respectively. Beetles were sampled by pitfall traps distributed in two 100-m transects. The fauna was characterized by diversity (H), evenness (J), abundance, dominance, frequency and constancy indexes. The influence of air temperature, relative humidity and rainfall was verified using stepwise regression. The carabids Abaris basistriatus Chaudoir, Odontochila nodicornis (Dejean) and Scarites sp. were classified as predominant species in both areas, while Selenophorus alternans Dejean only classified as predominant in the area under conventional tillage system, likewise for Megacephala sp. and Selenophorus seriatoporus Putz. in the no-tillage area. The predominant species showed just one population peak each year, usually observed from December to January. The pluvial precipitation influenced the occurrence of the carabids positively and significantly, with O. nodicornis and Megacephala sp. being the most demanding species in relation to the effect of humidity on their dispersal.
Faunistic analysis and populational fluctuation of Carabidae and Staphylinidae (Coleoptera) in Jaboticabal, State of São Paulo, Brazil